Investigation of relationship between weld cost and types of arc welding process / Noor Akmar Aman - Aman, Noor Akmar (2009)
This paper presents an investigation of relationship between weld cost and types of arc welding process. Weld deposition rate is the most useful information required in estimation of the welding cost and selection of welding condition. It is observed that the deposition rate varies very significantly with the changes in welding current and welding speed. Two approaches have to be carried out to understand this relationship. First, perform some welding samples and observed it. Second, analyze the relationship pattern and establish an empirical formula to predict the deposition rate for each welding process. The basic data collection such as current, voltage, weight and welding speed can be used to calculate the cost easily. The time recording during the welding process are also taken to get the speed/min. As a result of knowing all the information, the cost of project can be known before the project is started. It helps to planning a project wisely without expenses much time and money.